HUBUNGAN POLA ASUH ORANG TUA TERHADAP TINGKAT AGRESIVITAS ANAK TUNAGRAHITA RINGAN KELAS III SDLB YPPB KARIMUN - Eka Lenggang Dianasari; Yarliani; Zulfiana Dessyka Putri; Karunia Yulinda Khairiyah; Retno Triswandari (JURNAL JUDIKHU, 2022)
This study aims to determine the relationship between parenting patterns and the level of aggressiveness of mild mentally retarded class III SDLB YPBB Karimun. This study uses descriptive research methods with a qualitative approach the technique used, data collection through interviews with parents of students and children. the subject is a child with mild mental retardation in SDLB YPBB Karimun and has a tendency to aggressive behavior. The results of this study indicate that the dominant parenting pattern based on parenting theories is: permissive because parents are busy working everyday and do not pay attention to their children. Due to economic factors that make parents busy working everyday looking for sustenance. The dominant behavior is: fighting, kicking, hitting, aggressive behavior includes forms of physical aggressiveness and verbal aggression that are often with other friends during breaks.